1993
DOI: 10.1007/bf02164841
|View full text |Cite
|
Sign up to set email alerts
|

Dreidimensionale computertomographische Darstellung des bezahnten Alveolarkamms

Abstract: Human bone segments of the toothed jaw with ten upper and ten lower teeth were scanned by high resolution computer tomography in continuous parallel axial and coronal slices (Somaton plus, Siemens). In both directions scanning was performed to 1 mm and 2 mm thicknesses and at 1 mm and 2 mm intervals. The jaw segments were dissected analogously in 1 mm thick slices. Contact films of the corresponding bone segments were exposed and then histological thin sections prepared. The statistical comparison between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…Although a high degree of accuracy has been reported in earlier publications [10,14,18,19,22,25] all measurements in the present study were carried out at least twice. Although a high degree of accuracy has been reported in earlier publications [10,14,18,19,22,25] all measurements in the present study were carried out at least twice.…”
Section: Discussionmentioning
confidence: 66%
“…Although a high degree of accuracy has been reported in earlier publications [10,14,18,19,22,25] all measurements in the present study were carried out at least twice. Although a high degree of accuracy has been reported in earlier publications [10,14,18,19,22,25] all measurements in the present study were carried out at least twice.…”
Section: Discussionmentioning
confidence: 66%
“…In the literature, data about the accuracy of computed tomography has been described by several authors. Solar et al (2000) [12] reported an accuracy of -0.53 -0.45 mm, Fuhrmann et al (1993) [16] reported an accuracy of 0.3 -0.5 mm, and Lindh 1995 [13] an accuracy of 0.1 -1.3 mm. However, these investigators concentrated [17] concluded that the average deviation was 0.1-0.3 mm, and a dose reduction of 75% had no effect on the results.…”
Section: Ctmentioning
confidence: 99%
“…[5] tiber die nachweisliche InterpretationsmSglichkeit der Umgebungsstrukturen yon Wurzeln im CT, hat diese Untersuchung zum Ziel, die bestehenden dentoalveol~en Verh~iltnisse der vier Unterkieferinzisiviwurzeln in FRS und CT darzustellen. Ist eine topographische Beurteilung anhand des FRS m6glich?…”
Section: Literaturiiberblickunclassified